2016
DOI: 10.1161/jaha.116.003221
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐Effectiveness of Ivabradine for Heart Failure in the United States

Abstract: BackgroundIvabradine is a heart rate–lowering agent approved to reduce the risk of hospitalization for worsening heart failure. This study assessed the cost‐effectiveness of adding ivabradine to background therapy in the United States from the perspective of a commercial or Medicare Advantage payer.Methods and ResultsA cost‐effectiveness, cohort‐based Markov model using a state transition approach tracked a cohort of heart failure patients with heart rate ≥70 beats per minute in sinus rhythm who were treated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 14 publications
0
35
0
Order By: Relevance
“…Altogether, the geographic regions of the populations in the 64 publications encompassed 15 different countries: the most commonly identified nations included the USA ( n = 16 [25%]) [15–30], the UK ( n = 16 [25%]) [31–46] and Canada ( n = 5 [8%]) [24, 47–50]. A total of 48 (75%) publications included in this review reported their source of funding [15, 16, 18, 22, 24–35, 3742, 44, 45, 47, 48, 50–71]. Of the included publications, the most commonly reported pharmacologic treatments administered to patients with HF included eplerenone ( n = 12 [19%]), ramipril ( n = 11 [17%]) enalapril ( n = 8 [13%]) and ivabradine ( n = 6 [9%]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Altogether, the geographic regions of the populations in the 64 publications encompassed 15 different countries: the most commonly identified nations included the USA ( n = 16 [25%]) [15–30], the UK ( n = 16 [25%]) [31–46] and Canada ( n = 5 [8%]) [24, 47–50]. A total of 48 (75%) publications included in this review reported their source of funding [15, 16, 18, 22, 24–35, 3742, 44, 45, 47, 48, 50–71]. Of the included publications, the most commonly reported pharmacologic treatments administered to patients with HF included eplerenone ( n = 12 [19%]), ramipril ( n = 11 [17%]) enalapril ( n = 8 [13%]) and ivabradine ( n = 6 [9%]).…”
Section: Resultsmentioning
confidence: 99%
“…Most of the publications provided reasonable details in relation to the types of modelling approaches employed (Table 1). The most common modelling approaches used included a Markov cohort model type ( n = 28 [41%]) [15, 17, 19, 22, 23, 26, 27, 32–34, 3840, 44, 48, 49, 51, 52, 58, 6669, 72–76]. Given the versatility of the Markov model approach in adopting different types of health states patients can potentially experience, this method was further categorized into health state classifications.…”
Section: Resultsmentioning
confidence: 99%
“…Pharmacologic therapies, particularly “standard of care” treatments such as ACEI, ARBs, and beta‐blockers, are generally highly cost‐effective (ICER < $10,000/QALY gained) . Ivabradine, approved in the United States in 2015 for HFrEF, is estimated to provide both a cost‐savings and QALY benefit compared with standard of care among the commercially insured, and is cost‐effective ($24,920/QALY gained) among Medicare Advantage patients . Eplerenone, an aldosterone antagonist, has been demonstrated as consistently cost‐effective (ICER < $50,000/QALY gained) compared with standard of care in the post‐myocardial infarction HF population, with some estimates as low as $11,393/QALY gained .…”
Section: Discussionmentioning
confidence: 99%
“…40,41 Ivabradine, approved in the United States in 2015 for HFrEF, is estimated to provide both a cost-savings and QALY benefit compared with standard of care among the commercially insured, and is cost-effective ($24,920/ QALY gained) among Medicare Advantage patients. 42 Eplerenone, an aldosterone antagonist, has been demonstrated as consistently costeffective (ICER < $50,000/QALY gained) compared with standard of care in the post-myocardial infarction HF population, with some estimates as low as $11,393/QALY gained. 43,44 Nonpharmacologic therapies such as cardiac resynchronization therapy and implantable cardioverter defibrillators are generally cost-effective, with ICERs ranging from $20,000 to $90,000/QALY gained.…”
Section: Discussionmentioning
confidence: 99%
“…We fitted six standard functions (exponential, Weibull, Gompertz, log‐normal, log‐logistic, and generalized gamma) to the observable data, with the final choice for the base case analysis made on the basis of Akaike information criterion and Bayesian information criterion scores. Mortality rates in the model population never went below those in the general English population because, in these cases, the model was programmed to use general population mortality data adjusted for cardiovascular mortality …”
Section: Methodsmentioning
confidence: 99%